Comparing response blocking and response interruption/redirection on levels of motor stereotypy: Effects of data analysis procedures. Issue 4 (23rd October 2019) - DeRosa, Nicole M.; Novak, Matthew D.; Morley, Allison J.; Roane, Henry S.
Abstract : Autism spectrum disorder (ASD) is marked by deficits in social communication and the presence of restrictive and/or repetitive behaviors or interests. Motor stereotypy is a form of repetitive behavior that is common in ASD. Response Interruption and Redirection (RIRD) and response blocking (RB) are two interventions found to be efficacious in reducing motor stereotypy. However, the current literature presents with inconsistencies regarding the relative efficacy of these two procedures. Thus, we sought to replicate and extend previous literature by evaluating the efficacy of both interventions on reducing motor stereotypy among 3 individuals with ASD. We also sought to evaluate how variations in data analysis affected the interpretation of treatment outcomes. Results indicated that both interventions were equally efficacious at reducing stereotypy when analyzing data exclusive of treatment‐implementation time. However, when analyzing total session time data, RB produced greater and more sustained reductions in stereotypy across all participants. These results emphasize the importance of data analysis decision‐making in evaluating intervention outcomes.